2003
DOI: 10.1097/01.alc.0000078828.49740.48
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fusel Oil on Animal Hangover Models

Abstract: The fusel oil in whisky had no effect on the ethanol-induced emetic response, but it suppressed taste-aversion behavior in animal models of hangover symptoms. These results suggest that the fusel oil in whisky alleviates hangover, contrary to the common belief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Such a small difference in the amount of major volatile congeners between the 2 differently aged whiskies did not likely affect the duration of LORR, because the neurodepressive substances in major volatile congeners show a relatively large LD 50 (1.87-10.17 g/kg dose for rat, per os; The Merck Index, 1996). Contrary to popular belief, Hori et al (2003) suggested that fusel oils in whisky alleviate hangovers. Thus, volatile congeners are also unlikely involved in the prolongation of LORR found by whisky maturation.…”
Section: Discussionmentioning
confidence: 83%
“…Such a small difference in the amount of major volatile congeners between the 2 differently aged whiskies did not likely affect the duration of LORR, because the neurodepressive substances in major volatile congeners show a relatively large LD 50 (1.87-10.17 g/kg dose for rat, per os; The Merck Index, 1996). Contrary to popular belief, Hori et al (2003) suggested that fusel oils in whisky alleviate hangovers. Thus, volatile congeners are also unlikely involved in the prolongation of LORR found by whisky maturation.…”
Section: Discussionmentioning
confidence: 83%
“…), and at the bottom is mostly water. Fusel alcohols are most volatile at lower ethanol concentrations and tend to collect in the intermediate region where ethanol concentration is approximately 45% (v/v) [76]. In continuous distillation columns, fusel alcohol removal is accomplished by drawing a solution of water, ethanol, and fusel alcohols from the center of the rectifier (Figure 4).…”
Section: Fusel Alcoholsmentioning
confidence: 99%
“…Some of these alcohols are aromatic and are associated with strong tastes and pungent odours. Used sparingly, fusel alcohols and esters can contribute positively to foods and beverage flavours, but at higher concentrations, they are associated with unpleasant flavours and "hangover" symptoms [76]. These compounds can be detrimental to yeast growth; therefore, their removal is essential in maintaining efficient fermentation [10,[76][77][78].…”
Section: Fusel Alcoholsmentioning
confidence: 99%
“…The content and composition of FAs can make rice wine full-bodied, round, soft, and harmonious [ 8 , 9 ], which are organoleptic properties used to identify different wine products [ 6 ]. However, excessive FA contents can degrade the quality of rice wine and cause headaches, nervous hyperemia, and dizziness in consumers, in addition to giving the products a bitter-astringent taste or turbid/cloudy appearance [ 7 , 10 , 11 ]. Therefore, the FA content in rice wine must be controlled within a certain range, and the problem of high FA contents in the traditional brewing of rice wine has attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%